Learning Internet Explorer 4.0 (ViaGrafix OklahomaUS, 1998)
Gives an introduction to the Internet and the World Wide Web and discusses various features of this software to accomplish various activities viz. searching the Internet, sending e-mail, using file transfer protocol {FTP}. Includes a rating of various Internet sites.
Located in the Learning Resource Centre